Efficiency improvement of P3CT-Na based MAPbI3 solar cells with a simple wetting process. (4th June 2021) - Kassou, Said; Wu, Jia-Ren; Thakur, Diksha; Chandel, Anjali; Chiang, Shou-En; Cheng, Kai-Jen; Chen, Sheng-Hui; Shen, Ji-Lin; Chang, Sheng Hsiung
Abstract: The averaged power conversion efficiency of polyelectrolytes (P3CT-Na) based MAPbI3 solar cells can be increased from 14.94% to 17.46% with a wetting method before the spin-coating process of MAPbI3 precursor solutions. The effects of the wetting process on the surface, structural, optical and excitonic properties of MAPbI3 thin films are investigated by using the atomic-force microscopic images, x-ray diffraction patterns, transmittance spectra, photoluminescence spectra and Raman scattering spectra. The experimental results show that the wetting process of MAPbI3 precursor solution on top of the P3CT-Na/ITO/glass substrate can be used to manipulate the molecular packing structure of the P3CT-Na thin film, which determines the formation of MAPbI3 thin films.